Investigation of IL-17A Serum Levels in Patients with Nonmelanoma Skin Cancer. (18th June 2021) - Ghahartars, Mehdi; Sedaghat, Fatemeh; Khajavi, Elham; Nejat, Amir Ali; Malekzadeh, Mahyar; Ghaderi, Abbas; Fattahi, Mohammad Javad
Abstract : Background . Role of interleukin 17A (IL-17A) in carcinogenesis and cancer growth is controversial. Although some researches support its antitumor activity, some others suggest that it promotes the growth and development of different types of cancer including skin cancer by activation of STAT3. Although the function of the cytokines such as IL-17A has been extensively studied in various types of cancer, nonmelanoma skin cancer (NMSC) has not received much attention. Therefore, the present study was aimed to investigate the serum levels of IL-17A in NMSC patients. Methods . This cross-sectional study was performed on 60 patients with basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) as well as 57 age-sex matched healthy individuals as control group. Measurement of IL-17A serum levels in both case and control groups was performed by a commercially reliable sandwich enzyme-linked immunosorbent assay (ELISA) kit. Results . In this study, we observed that IL-17A serum levels in NMSC patients were significantly higher than the control group P < 0.001 . Also, both BCC and SCC patients had higher levels of IL-17A in their sera in comparison to the controls (P = 0.001 and P < 0.001, respectively). However, there was no significant difference between SCC and BCC patients regarding serum levels of IL-17A. Conclusion . According to our results, it can be concluded that IL-17A may play a role in inducing the growth and progression of NMSC and it can be used as a therapeutic target in these patients in future.